CD36 overexpression predisposes to arrhythmias but reduces infarct size in spontaneously hypertensive rats: gene expression profile analysis - Neckář, Jan; Šilhavy, Jan; Zídek, Václav; Landa, Vladimír; Mlejnek, Petr; Šimáková, Miroslava; Seidman, J G; Seidman, Christine; Kazdová, Ludmila; Klevstig, Martina; Novák, František; Vecka, Marek; et al. (Physiological genomics, 2012)
CD36 fatty acid translocase plays a key role in supplying heart with its major energy substrate, long-chain fatty acids (FA). Previously, we found that the spontaneously hypertensive rat (SHR) harbors a deletion variant of Cd36 gene that results in reduced transport of long-chain FA into cardiomyocytes and predisposes the SHR to cardiac hypertrophy. In the current study, we analyzed the effects of mutant Cd36 on susceptibility to ischemic ventricular arrhythmias and myocardial infarction in adult SHR-Cd36 transgenic rats with wild-type Cd36 compared with age-matched SHR controls. Using an open-chest model of coronary artery occlusion, we found that SHR-Cd36 transgenic rats showed profound arrhythmogenesis resulting in significantly increased duration of tachyarrhythmias (207 ± 48 s vs. 55 ± 21 s, P < 0.05), total number of premature ventricular complexes (2,623 ± 517 vs. 849 ± 250, P < 0.05) and arrhythmia score (3.86 ± 0.18 vs. 3.13 ± 0.13, P < 0.001). On the other hand, transgenic SHR compared with SHR controls showed significantly reduced infarct size (52.6 ± 4.3% vs. 72.4 ± 2.9% of area at risk, P < 0.001). Similar differences were observed in isolated perfused hearts, and the increased susceptibility of transgenic SHR to arrhythmias was abolished by reserpine, suggesting the involvement of catecholamines. To further search for possible molecular mechanisms of altered ischemic tolerance, we compared gene expression profiles in left ventricles dissected from 6-wk-old transgenic SHR vs. age-matched controls using Illumina-based sequencing. Circadian rhythms and oxidative phosphorylation were identified as the top KEGG pathways, while circadian rhythms, VDR/RXR activation, IGF1 signaling, and HMGB1 signaling were the top IPA canonical pathways potentially important for Cd36-mediated effects on ischemic tolerance. It can be concluded that transgenic expression of Cd36 plays an important role in modulating the incidence and severity of ischemic and reperfusion ventricular arrhythmias and myocardial infarct size induced by coronary artery occlusion. The proarrhythmic effect of Cd36 transgene appears to be dependent on adrenergic stimulation.
Keywords: antigeny CD36; Animals; CD36 Antigens; genetická predispozice k nemoci; Genetic Predisposition to Disease; stanovení celkové genové exprese; Arrhythmias, Cardiac; krevní tlak; Rats, Inbred SHR; Male; Myocardial Infarction; krysa rodu Rattus; potkani inbrední SHR; zvířata; mužské pohlaví; Blood Pressure; Rats; Gene Expression Profiling; srdeční arytmie; infarkt myokardu